METODE PEMBINA DALAM PEMBINAAN AKHLAKUL KARIMA SANTRI PONDOK PESANTREN ALKHAIRAAT MADINATUL ILMI DOLO - Nurmaya Medopa; MZ Muttaqien (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to see the methods applied by the coaches in fostering the morality of students at the Madinatul Ilmi Dolo Islamic Boarding School. This type of research is qualitative research. Methods of collecting data through observation, interviews, and documentation. The results of this study are that there are five methods applied by the supervisors of the Madinatul Ilmi Dolo Islamic Boarding School, namely the Uswah method (exemplary), the Ta'widiyah method (Habitat), the Mua'Iza method (Advice), the supervision method, the Reward and Punishment method.